Integration of Islamic Religious Education Values with Independent Curriculum: Opportunities and Challenges in Elementary Schools: Penelitian - Khaerunnisa; Riska Damayanti; Muhammadong (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Implanting teachings and values in Islamic Religious Education (PAI) since elementary school age is an important foundation in shaping students who have strong faith, commendable morals, and a sense of responsibility. The presence ofthe Merdeka Curriculum as a new learning system provides freedom for educators to develop moral and spiritual aspects through student -centered approaches and based on real life contexts. This study aims to evaluate the extent to which PAI values can be integrated optimally in the implementation of an independent curriculum at the elementary scl level, as well as examining the opportunities and obstacles that accompany it. This study uses a literature study method with a descriptive-qualitative approach, utilizing references from various academic publications, curriculum policies, and educational implementation reports. The findings show that the independent curriculum provides great potential for strengthening religious values, such as through the integration of Pancasila student profiles, freedom to design learning, as well as the implementation of value-oriented projects. However, a number of obstacles also emerged, including the limitations of teacher understanding of the value integration model, the disparity of learning facilities, and the need for sustainable training for educators. Therefore, the synergy between various parties, especially schools, teachers, parents, and government is the key in ensuring PAI's values are truly manifested in the educational process, not only theoretical. This study is expected to be a conceptual contribution in designing contextual religious education and in harmony with today's national curriculum policy.